Adaptive tuned mass damper with shape memory alloy for seismic application. (15th November 2020) - Huang, Haoyu; Mosalam, Khalid M.; Chang, Wen-Shao
Highlights: Innovative use of smart materials. Development of a novel Tuned Mass Damper system to reduce the seismic response. Adjusting the dynamic properties of shape memory alloy by changing its in-service temperature. Retuning the structure after change of dynamic properties. Abstract: When the characteristics of the main structure are changed, tuned mass damper (TMD) is easy to meet off-tuning problem. The object of this study is to develop a TMD with shape memory alloy (SMA) to reduce the vibration caused by off-tuning under seismic excitations. By materials characterisation of SMA, when the working temperature rises from −40 °C to 65 °C, the stiffness increases and the equivalent damping ratio drops. The SMA-based TMD was installed on a steel frame and tested under earthquake loading. The results show the SMA-based TMD is able to reduce the seismic response in the range of 34.09–47.77% at the tuned condition. However, by changing the main structural mass, the TMD was easy to be off-tuned. To retune the TMD, the SMA was heated and cooled for the TMD to resonate with the natural frequency of the main structure. When the SMA is cooled, the peak and RMS accelerations can be effectively reduced by up to 23.98% and 35.51%, respectively. It was found that the SMA-based TMD performs well if the frequency change of the main structure is in the same order. But when the temperature of SMA is increased higher than 19 °C, the damping ratio of SMA decreases, which causes a less effectiveness in reducing the vibration. In the future, the combinations of multiple SMA bars in TMD should be studied, and the applications of SMAs with higher phase transformation temperature can be investigated to improve the sensitivity while heating.